Dysregulation of trophic factors contributes to diabetic retinopathy in the Ins2Akita mouse. (May 2020) - Araújo, Rute S.; Silva, Maria S.; Santos, Daniela F.; Silva, Gabriela A.
Abstract: Diabetic retinopathy (DR) is considered as a diabetes-related complication that can lead to severe visual impairments. By 2030, it is expected that 1 in 5 adults will suffer from the disease. Suitable animal models for chronic DR are essential for a better understanding of the pathophysiology and to further develop new treatments. The Ins2 Akita mouse is a type 1 diabetes model that shows signs of both early and late stages of DR, including pericyte loss, increased vascular permeability, increased acellular capillaries and neovascularization. To further characterize DR in the Ins2 Akita mouse model, we have evaluated the protein levels of the angiogenesis inducers vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) and the angiogenesis inhibitor pigment epithelium-derived factor (PEDF). Additionally, we have analyzed the protein expression profile of the glial markers ionized calcium binding adaptor molecule 1 (Iba1) and glial fibrillary acidic protein (GFAP) as well as of the chemokine monocyte chemoattractant protein 1 (MCP-1). In this study we demonstrate that, with disease progression, there is the development of an inflammatory response and an unbalanced expression of pro- and antiangiogenic factors in the neural retina and in the retinal pigment epithelium (RPE) of Ins2 Akita mice. Therefore, our data provide support for the diabetic retinopathy features detected in the Ins2 Akita retina, reflecting what is observed in the human pathology. Highlights: Reliable DR animal models that reproduce the whole spectrum of the disease are crucial to the development of new therapies. Ins2 Akita mouse model develops an inflammatory response in the retina, predominantly in early stages of DR. Ins2 Akita mouse model shows a dysregulation in pro- and antiangiogenic factors in the retina.